The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10339-015-0715-8
|View full text |Cite
|
Sign up to set email alerts
|

Which numbers do you have in mind? Number generation is influenced by reading direction

Abstract: In Western participants, small numbers are associated with left and larger numbers with right space. A biological account proposes that brain asymmetries lead to these attentional asymmetries in number space. In contrast, a cultural account proposes that the direction of this association is shaped by reading direction. We explored whether number generation is influenced by reading direction in participants from a left-to-right (UK) and a right-to-left (Arab) reading culture. Participants generated numbers rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 16 publications
3
22
3
Order By: Relevance
“…Confirming earlier researches, it was discovered that children and adults tend to have biases for big and small numbers respectively. Researchers have identified factors which can influence number generation by humans to include lateral head turn [15], mental state [22], reading direction [9], hand and mouth action [11] and composite body movement [5]. The study in [24] affirms previous findings revealing the effect of active head rotation on the randomization of numbers in adults who were observed to generate smaller numbers during left rather than right rotation.…”
Section: /14supporting
confidence: 75%
“…Confirming earlier researches, it was discovered that children and adults tend to have biases for big and small numbers respectively. Researchers have identified factors which can influence number generation by humans to include lateral head turn [15], mental state [22], reading direction [9], hand and mouth action [11] and composite body movement [5]. The study in [24] affirms previous findings revealing the effect of active head rotation on the randomization of numbers in adults who were observed to generate smaller numbers during left rather than right rotation.…”
Section: /14supporting
confidence: 75%
“…Conversely, a study by Fern andez, Rahona, Herv as, V azquez, and Ulrich (2011) demonstrated that number magnitude affects free gaze choice by showing that participants are more likely to choose to look left after fixating small numbers and right after fixating large numbers. Other studies showed similar left-to-right biases in RNG studies involving other effectors: finger tapping (Plaisier & Smeets, 2011;Vicario, 2012) and whole-body turns (G€ obel, Maier, & Shaki, 2015;Shaki & Fischer, 2014). Taken together, these production studies demonstrate that spatial-numerical biases do not only accompany bottom-up number processing but are also present during top-down number generation.…”
supporting
confidence: 73%
“…The MNL is a semantic long-term memory representation in which numbers are coded on a unidimensional conceptual space, horizontally organized in ascending order from left to right: small numbers are encoded on the left side and large numbers on the right side (Hubbard et al, 2005). This spatial organization is thought to emerge from cultural practices such as writing/reading direction (Göbel, 2015;Göbel, Maier, & Shaki, 2015;Göbel, Shaki, & Fischer, 2011; for a right-to-left spatial orientation of the MNL in non-Western cultures see Shaki, Fischer, & Göbel, 2012;Shaki, Fischer, & Petrusic, 2009). According to the MNL account, the SNARC effect emerges from an isomorphism (i.e., a direct mapping) between the position of a number on this semantic representation and the left-right coordinates of the external response locations.…”
Section: Introductionmentioning
confidence: 99%